Pembuatan Rumah Pangan Lestari di Desa Midang Making of Sustainable Food Houses in Midang Village - Fahruddin Fahruddin; Fortuna Syahna Syaqillah (Pascasarjana Universitas Mataram, 2021)
Food is anything that comes from biological sources and water, either processed or unprocessed, which is intended as food or drink for human consumption. This includes food additives, food raw materials, and other materials used in the preparation, processing and or manufacture of food or beverages. This food is very attached to the theme we are currently taking, namely